2017
DOI: 10.1177/2053951717720950
|View full text |Cite
|
Sign up to set email alerts
|

Data cultures of mobile dating and hook-up apps: Emerging issues for critical social science research

Abstract: The ethical and social implications of data mining, algorithmic curation and automation in the context of social media have been of heightened concern for a range of researchers with interests in digital media in recent years, with particular concerns about privacy arising in the context of mobile and locative media. Despite their wide adoption and economic importance, mobile dating apps have received little scholarly attention from this perspective -but they are intense sites of data generation, algorithmic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 44 publications
0
58
0
5
Order By: Relevance
“…Queer Theory has been used to critically examine the new mobilities McGlotten (2013) and changing spatiotemporal relationships Baudinette (2018) arising from our everyday interactions through dating apps. However overall, research on dating platforms 4 , both globally and in the small number of India specific studies, tends to focus on user experiences (Albury et al 2017;Dasgupta 2018) and/or platform affordances (Shah 2015;MacLeod and McArthur 2019;Ferris and Duguay 2019), leaving a critical cultural analysis of dating app industry production relatively unexamined. The handful of empirical qualitative studies on the industry dynamics of queer dating apps, such as Murray and Ankerson's (2016) research on the production of sociality through the design decisions of the founder of the lesbian dating app Datch 5 and Wang's (2019) exploration of labor practices involved in livestreams of Chinese gay mens dating app BlueD, show that industry dynamics can be extremely rich sites of analysis to understand the construction of queer possibilities through digital design.…”
Section: Approach: Queer Theory Meets Media Industry Studiesmentioning
confidence: 99%
“…Queer Theory has been used to critically examine the new mobilities McGlotten (2013) and changing spatiotemporal relationships Baudinette (2018) arising from our everyday interactions through dating apps. However overall, research on dating platforms 4 , both globally and in the small number of India specific studies, tends to focus on user experiences (Albury et al 2017;Dasgupta 2018) and/or platform affordances (Shah 2015;MacLeod and McArthur 2019;Ferris and Duguay 2019), leaving a critical cultural analysis of dating app industry production relatively unexamined. The handful of empirical qualitative studies on the industry dynamics of queer dating apps, such as Murray and Ankerson's (2016) research on the production of sociality through the design decisions of the founder of the lesbian dating app Datch 5 and Wang's (2019) exploration of labor practices involved in livestreams of Chinese gay mens dating app BlueD, show that industry dynamics can be extremely rich sites of analysis to understand the construction of queer possibilities through digital design.…”
Section: Approach: Queer Theory Meets Media Industry Studiesmentioning
confidence: 99%
“…Dating app users thus are not simply passive audiences in algorithms but also active players who can shape the algorithmic results (Albury et al, 2017). The effects are two-fold.…”
Section: Blued Browsing: Indexing Gay Men Into Standard Datamentioning
confidence: 99%
“…However, studies on dating apps have found that users are in fact familiar with the data structures and sociotechnical operations of the apps and thereby can actively act on the data to shape the algorithmic results (Albury et al, 2017;David & Cambre, 2016). For example, on Tinder, the number of profiles users are allowed to swipe for free is limited and a period of waiting is enforced before the next swipe.…”
Section: Algorithmic Socialitymentioning
confidence: 99%
See 1 more Smart Citation
“…Gay dating apps have been studied as methods of networking and hooking up (Race, 2015a(Race, , 2015b; conduits for sharing pornography and soliciting prostitution (Brennan, 2017;Phillips, 2015;Tziallas, 2015); and sites for data production (Albury et al, 2017;Lutz and Ranzini, 2017;Wang, 2018). This body of work explores the ways in which users create digital profiles to make quick information exchanges for sexual or romantic purposes.…”
Section: Introductionmentioning
confidence: 99%